PENGGUNAAN MEDIA PEMBELAJARAN VISUAL TERHADAP HASIL BELAJAR DESAIN PRODUK DI SMKN 4 PADANG - Drs. Abd. Hafiz, M.Pd., AULIA ARIFANI, Drs. Erwin A, M.Sn., (Serupa The Journal of Art Education, 2018)
The background of this research is research is the low of the result of student’s learning in Product Design subject of SMKN 4 Padang. The am of this research is of describe the effect of using visual prezi media to increase of the result of student’s learning. The method of the research is experiment with using (purposive sampling) in technique data collection. After hypothesis testing is obtained tcount = 7,995 and ttable = 2.037, this indicates that tcount> ttabel. It can be concluded that the result of student’s learning in experiment class with using visual prezi media differ significantly compare. With control class without using visual prezi media and very influence to result of student’s learning. Therefore, it recommended for all the teachers to using visual prezi media in learning process.Keywords: Influence, Media, Learning, Learning Outcomes.